POLA PRODUKSI PIGMEN MONASCUS OLEH MONASCUS SP. KJR 2 PADA MEDIA BIJI DURIAN VARIETAS PETRUK MELALUI FERMENTASI PADAT - Puspitadewi, Stephanie Rosarie Dina; Srianta, Ignatius; Kusumawati, Netty (Jurnal Teknologi Pangan dan Gizi, 2016)
Angkak (red yeast rice) is rice fermented by Monascus sp. Monascus sp. KJR 2 is an isolate from red yeast rice in Kertajaya area. Based on previous study, it is known that KJR 2 is a potential isolate to produce pigments. Petruk durian is kind of tropical fruit that developed in Indonesia. Chemical composition of Petruk durian seeds are 33.68% of starch, 4.13% of protein, 1.00% of fat, 1.62% of minerals, and 84.06% of moisture in dry basis. A sorted Petruk durian seeds were boiled in Ca(OH)2, washed, and peeled-off the skin. Durian seeds were cut into cubes (Â±1 cm3), sterilized, and inoculated with Monascus sp. KJR 2 starter culture. It was incubated for 16 days with sampling on 4th, 6th, 8th, 10th, 12th, 14th, and 16 th days and was analyzed for the ethanol-soluble pigments, water-soluble pigments, and Total Mould. This study was conducted with four (4) replications and regression analysis was used to determine the correlation between fermentation time and Monascus sp. KJR 2 pigments production. Growth of Monascus sp. KJR 2 increased up to 4th day (6,4592 log cfu/g), stationary phase occurred at 6th day (6,3532 log cfu/g) up to 12thday (6,7213 log cfu/g), and death phase begin at 14thday (6,5944 log cfu/g). Production of ethanol-soluble red and yellow pigments increased up to 10thday (1,032 AU/g and 0,866 AU/g), whereas production of orange pigments up to 12thday (0,573 AU/g). Production of water-soluble yellow, orange, and red pigments increased up to 14 th day with yields at 6,458 AU/g, 3,781 AU/g, and 3,265 AU/g.